COVID-19 outbreaks in long term care facilities for elderly during periods of Delta and Omicron variants predominance in Spain (Boletín Epidemiológico Semanal, 2023)
Introduction: Throughout the COVID-19 pandemic, several outbreaks of SARS-CoV-2 in long-term care facilities (LTCF) for elderly have been reported worldwide, even after high vaccination coverage, especially with the arrival of SARS-CoV-2 Omicron variant. The aim of this study is to characterize those outbreaks reported voluntarily during the Delta and Omicron periods in Spain and to compare attack rates, hospitalised cases and deaths in residents and staff members between both periods.Method: The information has been collected following the protocol developed by the European Centre for Disease Prevention and Control (ECDC). A descriptive analysis of outbreaks reported from June-2021 to August-2022 has been performed. Attack rates (AT) and percentage of hospitalised cases and deaths by Delta or Omicron period have been calculated for residents and staff members.Results: 405 outbreaks with 6.389 cases among residents and 1.859 cases among staff have been studied. 98,5% of resident cases and 96% of staff cases were fully vaccinated (primary series of vaccination completed). Attack rates (AT) in residents and staff members was higher during the Omicron period (25.1% vs 15.5% and 10.8% vs 5.9%, respectively). The percentage of severe cases (hospitalised cases and deaths) was lower in the Omicron period (in residents and staff members).Conclusions: Omicron period is characterized by high transmissibility with outbreaks with higher AT than Delta period, but lower severity (hospitalised cases and deaths), both for residents and staff members.
Keywords: COVID-19; Elderly long term care facilities; Nursing homes; Outbreaks; Surveillance; Omicron; Delta